Competency of assistant registrars in strategic management in higher education / Imran Mohamed @ Ismail - Mohamed @ Ismail, Imran (2014)
The purpose of this study was to identify the level of knowledge, skills and attitude among the assistant registrars as the middle manager towards strategic implementation in Universiti Teknologi MARA. It is also aim to identify the level of successful strategic implementation and the relationship between knowledge, skills and attitude towards the success of strategic implementation in higher education. Seven hypotheses are tested base on four section of the questionnaire which is effective strategic implementation in higher education, knowledge of assistant registrars, skills of assistant registrars and; attitude of assistant registrars, adapted from various sources. 211 questionnaires were distributed to assistant registrar in grade range of N41 and N44 at Registrar's Office, faculties and branch campuses via group email. 120 of them had answered and returned the questionnaire completely. The data obtained were analysed and interpreted using demographic analysis, descriptive analysis, model adequacy checking for model and statistical analysis for model. The demographic findings revealed that male respondents, those in range from 35 to 39 years old, those having Masters' degree and those who have longer years of service perceived that they have had better skills in strategic management. In addition, the findings from this study support all the seven predetermined hypotheses. Overall, the findings of this study conclude that level of knowledge, skills and attitude in strategic management among assistant registrars is high despite of their different demographic group. Based on the findings, this study also provides recommendations for improvement of practices and future research.